Psychiatric in-patients' experience of being secluded in a specific hospital in Lesotho - Gloria M Ntsaba; Yolanda Havenga (AOSIS, 2007)
This qualitative, explorative, descriptive and contextual study was undertaken to explore and describe the experiences of psychiatric in-patients who are secluded in a specific hospital in Lesotho. Opsomming Hierdie kwalitatiewe, verkennende, beskrywende en kontekstuele studie is onderneem om die ervaring van psigiatriese binnepasiënte in afsondering in 'n spesifieke hospitaal in Lesotho te verken en te beskryf. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.